Interaction between infection, nutrition and immunity in tropical medicine - Pereira, P. C. M. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos, 2003)
Host nutritional state has an important role in susceptibility to bacteria, parasites, and viral infections. Infection precipitates the appearance of signs and symptoms of nutrition deficiencies in the undernourished; this can aggravate infection evolution. Infection stimulates specific and non-specific host defense mechanisms; these are directly influenced by the nutritional state of micro- and macronutrients. Immune alterations, which are closely related to nutritional status, markedly contribute to a higher susceptibility to infectious agents and can also contribute to worsening nutritional state, forming a vicious cycle.
Keywords: infection; nutrition; immunity; tropical diseases